Salvage Cytoreductive Surgery for Recurrent Endometrial Cancer. Issue 9 (1st November 2015) - Turan, Taner; Tasci, Tolga; Karalok, Alper; Ureyen, Isin; Kocak, Ozgur; Turkmen, Osman; Basaran, Derman; Tulunay, Gokhan
Abstract : Objective: The aim of this study was to determine the effect of salvage cytoreductive surgery (SCS) on overall survival (OS) among patients with recurrent endometrial cancer and if there is any predictor for residual tumor status. Methods: Between January 1993 and May 2013, data of 34 patients who had SCS for recurrent endometrial cancer were retrospectively analyzed. Overall survival was determined from SCS to last follow-up. Results: The surgical procedure was local excision without laparotomy in 12 patients, and optimal cytoreduction (no visible disease) was achieved in 24 of 34 patients. There were no perioperative deaths. None of the factors was associated with achievement of optimal cytoreduction. Five-year OS rates were 37% and 27% for the entire cohort and for the laparotomy group, respectively. For the entire cohort, disease-free interval (from initial surgery to recurrence), adjuvant therapy after initial surgery, CA-125 level at recurrence, multiplicity of recurrence, surgical procedure, and optimal cytoreduction and for the laparotomy group adjuvant treatment and optimal cytoreduction were associated with OS. In the laparotomy group, OS rates were 53 and 9 months in the patients who did and did not have optimal SCS, respectively. Conclusions: Significant survival benefit can be achieved with optimal resection. Prospective studies should be designed to define optimal cytoreduction and to determine the predictors of optimal cytoreduction achievement.